IMPLEMENTASI NILAI EDUPRENEURSHIP DALAM PENGEMBANGAN DAN PENGELOLAAN LEMBAGA KURSUS BAHASA INGGRIS “ENGLISH CENTER VOCATION” KAJEN - Ira Rihhadatul 'Aisy Haafidzoh; Irshofa Hany; Saadiyah Fajar; Titis Aji Nawang Wulan; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to describe the implementation of edupreneurship values in the development and management of the English language course institution, English Center Vocation Kajen. As a pioneering course in Pekalongan Regency, English Center Vocation Kajen integrates entrepreneurial principles with educational values to expand community access to English language skills. The study employs a qualitative descriptive approach, collecting data through in-depth interviews, observation, and documentation involving the institution’s leadership and instructors. The results indicate that the implementation of edupreneurship values includes institutional independence, innovation in learning services, social responsibility, and business sustainability. English Center Vocation Kajen manages its operations independently without government assistance, maintaining transparent financial management and adaptive marketing strategies through social media and community-based promotion. The principle of edupreneurship is reflected in human resource management that emphasizes professionalism, creativity, and humanistic service toward learners. Beyond profit orientation, the institution prioritizes social benefits through cross-subsidy policies, free training programs, and partnerships with schools to support equitable learning opportunities. Therefore, the implementation of edupreneurship values at English Center Vocation Kajen demonstrates an effective and sustainable model of non-formal educational management with a strong social spirit, which can serve as a replicable example for other educational institutions seeking to empower communities through education.